Pengaruh Minyak Biji Jinten Hitam (Nigella sativa L) terhadap Kadar Interleukin-4 : Effect of Black Cumin Seed Oil (Nigella sativa L) on Interleukin-4 Level - Tantri Rachmayani; Akrom Akrom; Titiek Hidayati (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Black cumin has a variety of efficacious substances, one of which is thymoquinon as an immunodulator, its role against Interleukin-4 with the subject of phase 2 clinical trials as an anti-inflammatory cytokine that is by inhibiting prostaglandin type E2 from arachidonic acid through induction resistance to cyclooxigenase-2. Aim to find out how the effect of Black Cumin Seed Oil in increasing levels of Interleukin-4. Randomized Clinical Trial study of 39 healthy participants of active smokers with the age of >18 years. Divided into 4 groups, namely Group 1 given placebo 3x1 capsules/day, group 2,3 and 4 given Black Cumin Seed Oil 3x1,3x2 and 3x3 capsules/day given for 30 days. Percentage il-4 using ELISA method. The results were analyzed using the One Way Annova method, with consecutive p-values (0.281 and 0.860) > 0.05 meaning there were meaningless differences between each treatment group. Based on the average percentage value of Interleukin-4, there was an increase in the MBJH treatment group of 3x1 capsules/day by 16,566% compared to the placebo group of 3x1 capsules/day by 13,995%.